3‐Phenylpropanoic Acid‐Based Phosphotyrosine (pTyr) Mimetics: Hit Evolution to a Novel Orally Active Protein Tyrosine Phosphatase 1B (PTP1B) Inhibitor. Issue 5 (18th March 2014) - Tang, Yan‐Bo; Liu, Jun‐Zheng; Zhang, Shu‐En; Du, Xin; Nie, Feilin; Tian, Jin‐Ying; Ye, Fei; Huang, Kai; Hu, Jin‐Ping; Li, Yan; Xiao, Zhiyan
Abstract Protein tyrosine phosphatase 1B (PTP1B) is a promising therapeutic target for type 2 diabetes. Herein, we report the evolution of a previously identified 3‐phenylpropanoic acid‐based PTP1B inhibitor to an orally active lead compound. A series of 3‐phenylpropanoic acid‐based PTP1B inhibitors were synthesized, and three of them, 3‐(4‐(9H‐carbazol‐9‐yl)phenyl)‐5‐(3, 5‐di‐tert‐butyl‐4‐methoxyphenyl)‐5‐oxopentanoic acid (9), 3‐(4‐(9H‐carbazol‐9‐yl)phenyl)‐5‐(4′‐bromo‐[1, 1′‐biphenyl]‐4‐yl)‐5‐oxopentanoic acid (10) and 3‐(4‐(9H‐carbazol‐9‐yl)‐2‐fluorophenyl)‐5‐(4‐cyclohexylphenyl)‐5‐oxopentanoic acid (16), showed IC50 values at sub‐micromolar level. Further in vivo evaluation indicated the sodium salt of 9 not only exhibited significant insulin‐sensitizing and hypoglycemia effects, but also decreased the serum levels of triglyceride and total cholesterol in high‐fat‐diet‐induced insulin resistance model mice. Preliminary in vivo pharmacokinetic studies on the sodium salt of 9 revealed its pharmacokinetic profile after oral administration in rats. These results provide proof‐of‐concept for the dual effects of PTP1B inhibitors on both glucose and lipid metabolisms.